Student Administration - Yuda Mulia Ramadhan; Vena Annisa Harahap (Universitas Muhammadiyah Enrekang, 2022)
Administration is a system related to an organization, or it can also be said that administration is an effort to achieve goals effectively and efficiently by employing groups in the cooperation model. Student administration is an attempt to regulate student education with the aim of organizing and managing education in schools so that activities are carried out according to the curriculum. The method used is a qualitative research method with a phenomenon-oriented research approach. The data obtained is in the form of data from observations, interviews, and documentation studies. The results obtained in this study are SMP IT AL-AFKARI placed on Deli Serdang which was established for 4 years to carry out student administration procurement in accordance with the concept of student administration which is implemented through student planning activities, student coaching, student evaluation, and transfer or mutation.